KEMAMPUAN AKADEMIK SISWA SEBAGAI PENDUKUNG KEPUTUSAN PENERIMA BEASISWA DENGAN METODE PROFILE MATCHING (STUDI KASUS SMA N 4 PADANGSIDIMPUAN) - Alwendi Alwendi; Yusra Fadillah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
SMA Negeri 4 Padang sidimpuan is a government agency engaged in education. At SMA N 4 Padangsidimpuan which already has a scholarship program for underprivileged students. Scholarships are gifts in the form of financial assistance given to individuals with the aim of being used for the continuity of the education being taken. Scholarship programs are held to ease the burden on students and especially for parents who do it selectively according to the type of scholarship being held. One of the methods used to search for prospective scholarship recipients is the application of Profile Matching because it is able to select the best alternative from a number of alternatives, in this case what is meant by alternatives, namely those who are entitled to receive scholarships based on specified criteria. The results of this study are the determination of underprivileged and high-achieving scholarship receipts into the ranking based on the calculation of the Profile Matching method that has been applied. From the existing ranking results will have the highest Profile Matching score who gets a scholarship and the application of the Profile Matching method into the application, ranking students according to predetermined criteria.